Invasion dynamics and elevational range expansion of insects in tropical agricultural landscapes of Wonosobo, Central Java, Indonesia - SAKINA ENOVA RAHMADHANI; SIBRINA SALSABILA; ROI ANDRIANTO; SYARIFAH HASNA ROSYIDA; QUROTUL AINIA; ARU DEWANGGA; AHMAD DWI SETYAWAN (Nusantara Bioscience, 2025)
Abstract. Rahmadhani SE, Salsabila S, Andrianto R, Rosyida SH, Ainia Q, Dewangga A, Setyawan D. 2025. Invasion dynamics and elevational range expansion of insects in tropical agricultural landscapes of Wonosobo, Central Java, Indonesia. Nusantara Bioscience 17: 355-374. Biological invasions in tropical mountain agroecosystems are increasingly reported, yet the processes driving elevational range expansion of invasive insects remain poorly understood. This study examined invasion dynamics and elevational range expansion of insects across a gradient of lowland to highland agricultural landscapes in Wonosobo District, Central Java, Indonesia. Using a targeted sampling approach, we quantified invasion intensity with the Relative Invasiveness Index (RII) and elevational expansion with the Altitudinal Expansion Index (AEI). Functional feeding group composition and environmental drivers were further analyzed to evaluate invasion-related community reorganization. A total of 692 insect individuals were recorded, of which 295 individuals (42.6%) belonged to nine invasive or potentially invasive taxa. RII values were lowest at lowland (13.2%), highest at mid-elevation (53.6%), and moderately high at highland sites (48.7%). In contrast, AEI was only positive in highland systems (mean AEI = 45.7%; range: 38.7-59.6%), where upslope expansion was detected in saprophagous Diptera, with Leucostoma simplex showing the highest elevational shift (up to 856 m above historically documented limits). Functional composition shifted from herbivore-dominated assemblages at low elevation to predator-dominated at mid-elevation and saprophage-detritivore-dominated at high elevation, indicating functional homogenization under increasing invasion pressure. Canonical Correspondence Analysis revealed that elevation and light intensity were the primary drivers of upslope expansion, while temperature and wind exposure influenced invasion dominance. These findings demonstrate that elevational gradients in tropical agricultural landscapes function as invasion filters rather than biodiversity gradients, with mid-elevation systems acting as transitional invasion hotspots and highland systems representing high-risk zones for invasion-driven functional simplification. The study highlights the need for elevation-specific invasion risk zoning and early intervention strategies to mitigate emerging invasion threats in tropical mountain agroecosystems.